2004
DOI: 10.1007/s10628-005-0001-2
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond dynamics of transition processes in reaction centers of Rhodobacter sphaeroides

Abstract: The reaction center (RC) of purple bacteria is formed by three protein subunits (L, M, and H) bound with four bacteriochlorophyll (Bchl) molecules, two bacteriopheophytin (Bph) molecules, two quinone ( Q A and Q B ) molecules, and one atom of nonheme iron. Two of the four Bchl molecules for a special pair P (Bchl dimer), which is a primary electron donor.After excitation of the P electron, it is transferred along the active A-chain, leading to consecutive formation of the anion radicals Bchl -, Bph -, and duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This marked kinetic isotope effect indicates that the red-shift is caused by protein relaxations which comprise rearrangements of hydrogen bonds. The red-shift is followed by a reversal back to the original position with lifetimes of 3.5 and 8.5 ps in the presence of H 2 O and D 2 O respectively [32]. These kinetics, which are ascribed to the primary charge separation step from 1 P * RC;relaxed to the acceptor BChl A (see equation (21.3)), reflect a striking kinetic isotope effect on the primary charge separation step.…”
Section: Effects On Hydrogen Bonding On Light-induced Charge Separationmentioning
confidence: 89%
See 2 more Smart Citations
“…This marked kinetic isotope effect indicates that the red-shift is caused by protein relaxations which comprise rearrangements of hydrogen bonds. The red-shift is followed by a reversal back to the original position with lifetimes of 3.5 and 8.5 ps in the presence of H 2 O and D 2 O respectively [32]. These kinetics, which are ascribed to the primary charge separation step from 1 P * RC;relaxed to the acceptor BChl A (see equation (21.3)), reflect a striking kinetic isotope effect on the primary charge separation step.…”
Section: Effects On Hydrogen Bonding On Light-induced Charge Separationmentioning
confidence: 89%
“…Excitation of the Q X transition with 70 fs (FWHM) laser pulses at 600 nm revealed that the bleaching maximum of 1 P * RC is shifted to the red by about 4 and 5 nm with time constants of about 250 and 375 fs when the same sample material is suspended in buffer solutions containing H 2 O and D 2 O respectively [32]. This marked kinetic isotope effect indicates that the red-shift is caused by protein relaxations which comprise rearrangements of hydrogen bonds.…”
Section: Effects On Hydrogen Bonding On Light-induced Charge Separationmentioning
confidence: 99%
See 1 more Smart Citation